The historical and current research progress on jujube–a superfruit for the future. (1st August 2020) - Liu, Mengjun; Wang, Jiurui; Wang, Lili; Liu, Ping; Zhao, Jin; Zhao, Zhihui; Yao, Shengrui; Stănică, Florin; Liu, Zhiguo; Wang, Lixin; Ao, Changwei; Dai, Li; et al.
Abstract: Jujube ( Ziziphus jujuba Mill.), or Chinese date, is the most important species of Rhamnaceae, a large cosmopolitan family, and is one of the oldest cultivated fruit trees in the world. It originates from the middle and lower reaches of the Yellow River, the 'mother river' of the Chinese people. It is distributed in at least 48 countries on all continents except Antarctica and is becoming increasingly important, especially in arid and semiarid marginal lands. Based on a systematic analysis of the unique characteristics of jujube, we suggest that it deserves to be recognized as a superfruit. We summarized historical research achievements from the past 3000 years and reviewed recent research advances since 1949 in seven fields, including genome sequencing and application, germplasm resources and systematic taxonomy, breeding and genetics, cultivation theory and techniques, pest control, postharvest physiology and techniques, and nutrition and processing. Based on the challenges facing the jujube industry, we discuss eight research aspects to be focused on in the future.